2000
DOI: 10.1016/s0022-5347(05)67870-6
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor Kappa B Mediates Lipopolysaccharide-Induced Inflammation in the Urinary Bladder

Abstract: NF-kappaB mediates many features of urinary bladder inflammation induced by LPS. The NF-kappaB cascade is an important target for anti-inflammatory management of cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
31
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 32 publications
4
31
0
Order By: Relevance
“…15 The present results indicate that NF-B is a pathway commonly up-regulated as the bladder responds to other pro-inflammatory stimuli such as antigen and SP stimulation. In contrast to NF-B that was up-regulated by all three stimuli, LPS was the only stimulus to induce the transcription factor AP-1 and transcription factor E2F3.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 51%
See 3 more Smart Citations
“…15 The present results indicate that NF-B is a pathway commonly up-regulated as the bladder responds to other pro-inflammatory stimuli such as antigen and SP stimulation. In contrast to NF-B that was up-regulated by all three stimuli, LPS was the only stimulus to induce the transcription factor AP-1 and transcription factor E2F3.…”
Section: Signal Transduction Pathwaysmentioning
confidence: 51%
“…11 We also reported that intravesical inoculation of mice with LPS induced up-regulation of peptide receptors such as bradykinin-1 (BK1) 14 and NK1. 15 Moreover, we observed that LPS-induced cystitis was associated with activation of nuclear transcription factor B (NF-B). 15 Inhibition of NF-B with lactacystin blocked LPSinduced inflammation and NK1 receptor up-regulation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…It is of interest that proteasomes have previously been shown to be involved in LPS-induced degradation of IB (42)(43)(44)(45)(46). Current understanding of this pathway suggests that, after LPS activation of macrophages, a cascade of adaptors and kinases interacts with the intracytoplasmic domain of TLR4, leading to the phosphorylation and ubiquitination of IB, which is then degraded by the proteasome.…”
Section: Figurementioning
confidence: 99%